Efektifitas Latihan Birth Ball Terhadap Efikasi Diri Primipara dengan Persalinan Normal - Djudju Sriwenda; Yulinda Yulinda (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Stress, fear and anxiety are the factors which having contribution of pain perseption those influence labor process and birth experience.Birth ball is not only a non farmacological pain relief but also increasing emotional and psychlogical care. Self effiacy is a belief or an abiity to exert her ability to pass adversity in labor process. These is an important aspect which influence women motivation to make birth normally. It was quasi–experiment research. Treatment group was given birth ball exercise since 32 weeks of gestation until before labor process.Research period is from june until october 2014 at 5 (five) privat  midwife's private clinic and used consecutive sampling. The research analysis used t-independent to compare self efficacy level on control and treatment group that was taken at first self efficacy test. It also used t-independet on those group to compare self efficacy level at second test. In conclusion, there was influence of birth ball exercise to self efficacy of primiparous with normal labor, there was no difference on self efficacy level at 4 cm cervic dilatation on both groups, also there was 6.48 point of self efficacy level increase at 4 cm and 8 cm cervic dilatation after doing birth ball exercise. Birth ball exercise shoud be done since third trimester of pregnancy, which can be held integrated in antenatal class. There shoud be variety at physic exercise facility for pregnant woman and parturient at health services.